PROFIL BERPIKIR KRITIS SISWA SMP DALAM MEMECAHKAN MASALAH GEOMETRI DITINJAU DARI GAYA KOGNITIF VISUALIZER-VERBALIZER - Fardinah Fardinah; Mulyati Mulyati (CENDEKIA: JURNAL ILMIAH PENDIDIKAN, 2019)
This study discusses the critical thinking profile of SMP students in solving geometry problems. Critical thinking in this study refers to Facione's critical thinking, namely interpretation, analysis, evaluation, inference, eVIIIplanation and self regulation. The purpose of this study is to describe the critical thinking profile of SMP students in solving geometry problems in terms of the visualizer-verbalizer cognitive style so that this research is an eVIIIplorative study with a qualitative descriptive approach. The results of this study it was found that the critical thinking profile of students who have cognitive visualizer and verbalizer style in understanding problems can mention what is known and asked about the problem, but subjects with cognitive verbalizer style can eVIIIpress the contents of the problem using their own words even though some of the sentences still adopt from the problem. Whereas in terms of planning problem solving, carrying out plans and checking again, the subject of visualizer and verbalizer style tends to have the same profile. Keywords: Critical Thinking, Problem Solving , Cognitive Verbalizer-Visualizer